2021
DOI: 10.1249/jes.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Exercise-Induced Changes in Human Neuronal Networks

Abstract: Although several methods have been used to estimate exercise-induced changes in human neuronal networks, there are growing doubts about the methodologies used. This review describes a single motor unit–based method that minimizes the errors inherent in classical methods. With this method, it is now possible to identify human neuronal networks' changes due to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…The neural control mechanisms responsible for the modulation of motor unit discharge rate at different muscle–tendon lengths is not fully understood. Cortical and subcortical drives (Glover and Baker 2020 ; Türker 2021 ) are likely responsible for the adjustments in the neural drive to the tibialis anterior muscle as a function of its length-dependent variations in contractile properties during submaximal isometric contractions. However, peripheral afferent receptors may likely also play an important role in modulating the neural drive to muscle during force variations at different muscle–tendon lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The neural control mechanisms responsible for the modulation of motor unit discharge rate at different muscle–tendon lengths is not fully understood. Cortical and subcortical drives (Glover and Baker 2020 ; Türker 2021 ) are likely responsible for the adjustments in the neural drive to the tibialis anterior muscle as a function of its length-dependent variations in contractile properties during submaximal isometric contractions. However, peripheral afferent receptors may likely also play an important role in modulating the neural drive to muscle during force variations at different muscle–tendon lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that aerobic exercise can improve brain health and delay brain aging through mechanisms, such as strengthening neuronal connectivity, increasing neurotrophin synthesis and release, and promoting neural regeneration and synaptic reshaping 12 . Thus, aerobic exercise can serve a non‐pharmacological intervention for brain aging.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that aerobic exercise can improve brain health and delay brain aging through mechanisms, such as strengthening neuronal connectivity, increasing neurotrophin synthesis and release, and promoting neural regeneration and synaptic reshaping. 12 Thus, aerobic exercise can serve a nonpharmacological intervention for brain aging. However, whether aerobic exercise decreases aging-induced neuronal apoptosis, especially by mediating hippocampal DAPK1 expression whereby affecting cognitive function, remains unknown.…”
mentioning
confidence: 99%